Paradoxical dissociation between heart rate and heart rate variability following different modalities of exercise in individuals with metabolic syndrome: The RESOLVE study. (29th August 2020) - Boudet, Gil; Walther, Guillaume; Courteix, Daniel; Obert, Philippe; Lesourd, Bruno; Pereira, Bruno; Chapier, Robert; Vinet, Agnès; Chamoux, Alain; Naughton, Geraldine; Poirier, Paul; Dutheil, Frédéric
Abstract: Aims: To analyse the effects of different modalities of exercise training on heart rate variability (HRV) in individuals with metabolic syndrome (MetS). Methods and results: Eighty MetS participants (aged 50–70 years) were housed and managed in an inpatient medical centre for 21 days, including weekends. Physical activity and food intake/diet were intensively monitored. Participants were randomly assigned into three training groups, differing only by intensity of exercise: moderate-endurance-moderate-resistance ( re ), high-resistance-moderate-endurance ( Re ), and moderate-resistance-high-endurance ( rE ). HRV was recorded before and after the intervention by 24-hour Holter electrocardiogram. Although mean 24-hour heart rate decreased more in Re than re (–11.6 ± 1.6 vs. –4.8 ± 2.1%; P  = 0.010), low frequency/high frequency decreased more in re than Re (–20.4 ± 5.5% vs. + 20.4 ± 9.1%; P  = 0.002) and rE (–20.4 ± 5.5% vs. –0.3 ± 11.1%; P  = 0.003). Very low frequency increased more in Re than re (+121.2 ± 35.7 vs. 42.9 ± 11.3%; P  = 0.004). For all HRV parameters, rE ranged between re and Re values. Low frequency/high frequency changes were linked with visceral fat loss only in re (coefficient 5.9, 95% CI 1.9–10.0; P  = 0.004). By day 21, HRV parameters of MetS groups (heart rate –8.6 ± 1.0%, standard deviation of R-R intervals + 34.0 ± 6.6%, total power + 63.3 ± 11.1%; P  < 0.001) became closer to values of 50 aged-matched healthy controls. Conclusions: A 3-week residential programme with intensive volumes of physical activity (15–20 hours per week) enhanced HRV in individuals with MetS. Participants with moderate intensity of training had greater improvements in sympathovagal balance, whereas those with high intensity in resistance training had greater decreases in heart rate and greater increases in very low frequency. Modality-specific relationships were observed between enhanced HRV and visceral fat loss. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00917917.